(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Background: Bell’s palsy is a common type of hemifacial nerve paralysis with acute onset that happens without any recognizable or evident reason. Objective: To critically analyze and compare the efficacy of a nerve muscle stimulator, also known as an NMS device, in improving and developing the function of facial muscles in patients with Bell’s palsy throughout a holistic one-year duration. Methods: A prospective interventional study was conducted on 980 patients (aged 18–85) diagnosed with Bell’s palsy at clinic in Tashkent. All patients received standard physiotherapy combined with NMS therapy for four weeks. Assessments were conducted at baseline and after 3 months. Results: Statistically significant improvements were noted in all parameters measured, reflecting a significant enhancement. Muscle strength showed a dramatic increase from a baseline of 1.9±0.6 to a very impressive 4.0±0.5, with a p-value of less than 0.001, reflecting the statistical significance of this change; facial motor activity also showed significant improvement as well, rising from 3.2±1.0 to 8.1±0.8, also with a p-value of less than 0.001. In addition, muscle atrophy showed a significant reduction, and it is interesting to note that facial reflexes normalized in 84.5% of patients at the end of the therapy. Conclusion: Use of a nerve muscle stimulator has been seen to improve considerably the rehabilitation outcome realized by patients afflicted with Bell’s palsy. Since this modality has shown a positive impact on the healing process, it is critical that it be introduced into routine adjunct therapy provision in physiotherapy regimens put in place in the early phase of addressing such a condition.